Bibliographic research by Mokhtar BouananiAnalytical descriptive reading (مجلة إحالات, 2026)
This research seeks to highlight the efforts of a prominent Algerian scholar in the field ofbibliographic authorship. This is related to Prof. Dr. Mokhtar Bouanani, who made abundantcontributions in this field of knowledge. In order to introduce the reader - general or specialist - tohis most important bibliographic works, to determine their cognitive value, to clarify theirmethodological importance on the one hand, and to reveal some features of the bibliographic industry used in developing these works on the other hand.